Analysis of complex networks : from biology to linguistics - Dehmer, Matthias, 1968-; Emmert-Streib, Frank (Wiley-VCH, 2009)
Mathematical problems such as graph theory problems are of increasing importance for the analysis of modelling data in biomedical research such as in systems biology, neuronal network modelling etc. This book follows a new approach of including graph theory from a mathematical perspective with specific applications of graph theory in biomedical and computational sciences. The book is written by renowned experts in the field and offers valuable background information for a wide audience.